Engineering Chimeric Antigen Receptor T-Cells for Racing in Solid Tumors: Don’t Forget the Fuel - Irving, Melita; Vuillefroy de Silly, Romain; Scholten, Kirsten; Dilek, Nahzli; Coukos, George (Frontiers in Immunology, 2017)
T-cells play a critical role in tumor immunity. Indeed, the presence of tumor-infiltrating lymphocytes is a predictor of favorable patient prognosis for many indications and is a requirement for responsiveness to immune checkpoint blockade therapy targeting programmed cell death 1. For tumors lacking immune infiltrate, or for which antigen processing and/or presentation has been downregulated, a promising immunotherapeutic approach is chimeric antigen receptor (CAR) T-cell therapy. CARs are hybrid receptors that link the tumor antigen specificity and affinity of an antibody-derived single-chain variable fragment with signaling endodomains associated with T-cell activation. CAR therapy targeting CD19 has yielded extraordinary clinical responses against some hematological tumors. Solid tumors, however, remain an important challenge to CAR T-cells due to issues of homing, tumor vasculature and stromal barriers, and a range of obstacles in the tumor bed. Protumoral immune infiltrate including T regulatory cells and myeloid-derived suppressor cells have been well characterized for their ability to upregulate inhibitory receptors and molecules that hinder effector T-cells. A critical role for metabolic barriers in the tumor microenvironment (TME) is emerging. High glucose consumption and competition for key amino acids by tumor cells can leave T-cells with insufficient energy and biosynthetic precursors to support activities such as cytokine secretion and lead to a phenotypic state of anergy or exhaustion. CAR T-cell expansion protocols that promote a less differentiated phenotype, combined with optimal receptor design and coengineering strategies, along with immunomodulatory therapies that also promote endogenous immunity, offer great promise in surmounting immunometabolic barriers in the TME and curing solid tumors.